Electro‐Optic and Dielectric Studies on Quantum Dot Doped Nematic Liquid Crystal. Issue 1 (November 2015) - Kumar, Jitendra; Gupta, R. K.; Kumar, Sandeep; Manjuladevi, V.
Summary: Liquid crystals are shape anisotropic organic materials which find many applications in a wide variety of fields such as display technology, bioscience and surface science. On doping the liquid crystals with nanomaterials such as nanoparticles or carbon nanotubes the switching properties can be altered. In this report, the electro‐optic and dielectric properties of cadmium selenide quantum dots (CdSe QDs) doped nematic liquid crystal (NLC) is presented. The nematic liquid crystal was doped with different concentrations of the semiconducting QDs. The nematic to isotropic (N‐I) transition temperature for doped sample is comparable to that of pure NLC. The doped sample is found to have a lower threshold voltage than that of pure NLC. The value of threshold voltage decreases with increasing concentration of the QDs. The dielectric permittivity is estimated as a function of temperature in both planar and homeotropic geometry. Doping QDs led to increase in dielectric anisotropy in comparison with that of pure liquid crystal. The result showed that the incorporation of QDs into NLC provides a way to improve the performance of LC based devices.